A Warfare Metaphor and its Functional Aims in an Actual Armed Conflict – the Forty-Four Day War - Muradian, Gaiane (2022)
The present case study in general and the multimodal analysis of the warfare metaphor in particular tend to focus on the prevalence of metaphor framing related to news schemas documented over the period of the forty-four days of an actual war - the 2020 Nagorno-Karabagh war. Certain questions (Why was the warfare metaphor so widely used in this forty-four day war? How and in what ways did this type of metaphor realize its functional aims?) are addressed in the present case study by analyzing theoretical and empirical data on the subject and by advancing my own account of the functions of the warfare metaphor in war discourse presented in mass-mediated communication. Metaphor framing and its effects usually depend on words (the linguistic or verbal metaphor), however, such effects also depend on multimodal representations of the verbal metaphor, namely on the visual image. I therefore argue that metaphor framing and metaphor effects should be examined and explicitly described within the frames of multimodal analysis which can disclose how the convergence of verbal and the visual metaphor affects rhetorical war situations and increases the audience’s reception of the message of the war. Hence, this case study will show that the wartime metaphor, with the application of multimodality, conveys information of the war and impacts public opinion, thus striving to achieve positive outcomes. The results show that metaphor framing and the given type of metaphor is encountered in actual war to draw and capture public attention through emotionally charged multimodal devices aimed at informing and impacting public opinion, thus persuading and motivating the world to take urgent steps to stop the further escalation of the conflict. The usage of such metaphor framing closely connected with the context of war might result in certain outcomes illuminating that the warfare metaphor contributes to the understanding of complexities and abstractions of war discourse at large.
Keywords: the forty-four day war; news media; multimodality; warfare metaphor; metaphor framing; recontextualization